Heterologous expression reveals unique properties of Trk K+ importers from nonconventional biotechnologically relevant yeast species together with their potential to support Saccharomyces cerevisiae growth - Papoušková, Klára; Gómez, Marcos; Kodedová, Marie; Ramos, José; Zimmermannová, Olga; Sychrová, Hana (Yeast (Chichester, England), 2023)
In the model yeast Saccharomyces cerevisiae, Trk1 is the main K+ importer. It is involved in many important physiological processes, such as the maintenance of ion homeostasis, cell volume, intracellular pH, and plasma-membrane potential. The ScTrk1 protein can be of great interest to industry, as it was shown that changes in its activity influence ethanol production and tolerance in S. cerevisiae and also cell performance in the presence of organic acids or high ammonium under low K+ conditions. Nonconventional yeast species are attracting attention due to their unique properties and as a potential source of genes that encode proteins with unusual characteristics. In this work, we aimed to study and compare Trk proteins from Debaryomyces hansenii, Hortaea werneckii, Kluyveromyces marxianus, and Yarrowia lipolytica, four biotechnologically relevant yeasts that tolerate various extreme environments. Heterologous expression in S. cerevisiae cells lacking the endogenous Trk importers revealed differences in the studied Trk proteins' abilities to support the growth of cells under various cultivation conditions such as low K+ or the presence of toxic cations, to reduce plasma-membrane potential or to take up Rb+ . Examination of the potential of Trks to support the stress resistance of S. cerevisiae wild-type strains showed that Y. lipolytica Trk1 is a promising tool for improving cell tolerance to both low K+ and high salt and that the overproduction of S. cerevisiae's own Trk1 was the most efficient at improving the growth of cells in the presence of highly toxic Li+ ions.
Keywords: Biological Transport; yeasts; Saccharomyces cerevisiae; biologický transport; Cation Transport Proteins; Potassium; proteiny přenášející kationty; Saccharomyces cerevisiae Proteins; Trk importers; Saccharomyces cerevisiae - proteiny; potassium; ion transporters; homeostasis; Phylogeny; fylogeneze; Yarrowia; heterologous expression; draslík